Room-temperature synthesis of nanometric and luminescent silver-MOFs - Celis-Arias, Vanessa; Garduño-Wilchis, Ismael A.; Alarcón, Gilberto; González Chávez, Fernando; Garrido Guerrero, Efrain; Beltrán, Hiram I.; Loera-Serna, Sandra (Frontiers in Chemistry, 2023)
Three silver-MOFs were prepared by an optimized, room-temperature methodology starting from AgNO₃ and dicarboxylate ligands in water/ethanol yielding Ag2BDC, Ag2NDC (UAM-1) & Ag2TDC (UAM-2) in 38-48% (BDC=benzenedicarboxylate; NDC=1,8-naphthalene-dicarboxylate; TDC=p-terphenyl-4,4′′-dicarboxylate). They were characterized by PXRD/FT-IR/TGA/photoluminescence spectroscopy, and the former two by SEM. These materials started decomposing at 330ºC evidencing stability. The crystal structure for UAM-1 was determined by PXRD, DFT calculations, and Rietveld refinement, in general, the structure is of 3D nature, where the largest Ag-O bonding is interlinking 2D-layers. FTIR spectra revealed 1450 and 1680 bands (cm-1) of asymmetric stretching aniso-/iso-bidentate -COO coordination with 2/3-Ag atoms, accompanied by Ag-O bands in 780-740, all evidenced the formation of the network. XRD and SEM, unveil nanometric-scale crystals of Ag₂BDC, and UAM-1 developed micrometric single-stranded/agglomerated fibrillar particles of varying nanometric widths. Luminescence spectroscopy presented emission of Ag₂BDC, attributed to ligand-to-metal or ligand-to-metal-metal transitions, evidencing an energy transfer due to a short distance between adjacent BDC molecules. UAM-1 and UAM-2 have not shown luminescence emission attributable to ligand-to-metal transition, presenting only emission in UV. Stability of Ag₂BDC and UAM-1 was evaluated in PBS/DMEM/DMEM+FBS media by XRD, losing their crystallinity, and yielding AgCl due to soft-soft (Pearson's principle) affinity.